The Newtonians and the English Revolution, 1689-1720 - Jacob, Margaret C. (Cornell University Press, 2019)
This book offers a social history of Newtonian natural philosophy from its inception after the 1688 revolution in England until the 1720's. Ms. Jacob shows that the Newtonian world view was adopted by the Anglican church to support its own version of liberal Protestantism and its vision of a social and economic order that would be both Christian and capitalist. It was with Newton's consent, she asserts, that Newtonianism took on an ideological significance in the early Enlightenment. Using an interdisciplinary approach to subjects traditionally reserved for the history of science, church history, and intellectual history, she formulates a convincing new explanation for the triumph of Newtonianism.